New Exact Solutions for a Generalized Double Sinh-Gordon Equation - Gabriel Magalakwe; Chaudry Masood Khalique (Abstract and Applied Analysis)
We study a generalized double sinh-Gordon equation, which has applications in various fields, such as fluid dynamics, integrable quantum field theory, and kink dynamics. We employ the Exp-function method to obtain new exact solutions for this generalized double sinh-Gordon equation. This method is important as it gives us new solutions of the generalized double sinh-Gordon equation.